The philosophy of interrogative gaps in the Iraqi narrative after 2003 - Hamza, Sate' Jassim; Al-Taie, Rafal Hassan Taha (Al-Adab Journal, 2021)
Interrogative narrative gaps in narrative texts are among the important techniques in attracting and exciting the reader and increasing ones desire to read. Novel texts are based on narrative gaps, and the reader has the responsibility to consider them until the literary work is embodied and achieved. It cannot be overlooked, that the presence of gaps in the text represents a blocking or postponement of knowledge, which raises the reader's curiosity in accessing that blocked or postponed knowledge. The text presents questions waiting for answers, leading the reader to reach them in order to fill them in, as the text based on the gaps is based on dialogue and discussion. The Iraqi narratives represent a wide narrative space for these virtual spaces, especially the flowing narrative production after 2003, with all its political, social and cultural changes represented by this interval of time. Since the gap is related to the reader more than it is to the text, the reader must be responsible for revealing the place and space of the gap. For this reason, the idea of the research was born to monitor the interrogative gaps in the Iraqi novels, in order to shed light on them theoretically and in practice, and to show the important and pivotal role of the interrogative gaps in the Iraqi novels after 2003.